2007
DOI: 10.1590/s0102-79722007000100016
|View full text |Cite
|
Sign up to set email alerts
|

Estratégias de coping de mães de portadores de autismo: lidando com dificuldades e com a emoção

Abstract: ResumoEstudos têm apontado evidências de estresse em famílias de portadores de autismo. Neste processo, deve-se considerar as estratégias de coping utilizadas pelos familiares frente às circunstâncias adversas. O objetivo deste estudo foi verificar as estratégias de coping maternas frente a dificuldades dos portadores de autismo, assim como as estratégias das mães para lidar com as próprias emoções desencadeadas pelo estresse. Participaram 30 mães, entre 30 a 56 anos, cujos filhos apresentam diagnóstico de aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
32

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 31 publications
1
9
0
32
Order By: Relevance
“…The present study had as initial hypothesis a decrease in self-reported QoL of siblings and caregivers of children included in the autism spectrum (8)(9)(10)(11)(12) . Demographic data were collected in order to obtain an overview of the families and select the participants of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study had as initial hypothesis a decrease in self-reported QoL of siblings and caregivers of children included in the autism spectrum (8)(9)(10)(11)(12) . Demographic data were collected in order to obtain an overview of the families and select the participants of this study.…”
Section: Discussionmentioning
confidence: 99%
“…A study with 40 autistic children reported that these children, in their perception of the world, are happy, regardless of their functional deficits, as they reported QoL indexes that were similar to those of normal children (7) . However, it is noticed in the literature that those who frequently suffer the consequences of the autism framework are their family members (5,(8)(9)(10)(11)(12) . Parents or caregivers of children included in the autism spectrum may face tensions and therefore could benefit from a family-centered treatment proposals (10) .…”
Section: Introductionmentioning
confidence: 99%
“…Diante das dificuldades que se referem ao comportamento do filho, eles utilizam predominantemente as estratégias de ação direta e de aceitação. Para lidar com as emoções, recorrem preferencialmente à distração, busca de apoio social/religioso, inação e evitação (Schmidt et al, 2007).…”
Section: Estratégias De Coping E Desenvolvimento Da Resiliência Na Faunclassified
“…Of the 93 articles identified, 21 were classified into this categorya 13,33,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] . NOf the 140 relevant abstracts found in the CAPES database, 46 fell into this category.…”
Section: Communication Patterns and Family Relationsmentioning
confidence: 99%